TRANSFORMASI PACKAGING SEBAGAI UPAYA PENINGKATAN NILAI JUAL PRODUK PUPUK ORGANIK UMKM DI KELURAHAN KARANGWARU, KECAMATAN PLUPUH, SRAGEN - Nurdyastuti, Tri; Suroto, Suroto; Martiningsih, Dyah; Fatonah, Siti (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
Organic fertilizers play an important role in sustainable agriculture, especially in an era where awareness of environmental health is increasing. In Karangwaru Village, Plupuh District, Sragen, there are Micro, Small, and Medium Enterprises (MSMEs) that produce quality organic fertilizers. However, although their products have significant benefits, many MSMEs face challenges in terms of marketing, especially in terms of product packaging. In this context, packaging assistance is very important to help MSMEs in Karangwaru improve their packaging capabilities. The stages of the activity include Problem Identification, Counseling and Education, Packaging Design and Development Stages, Technical Training, Monitoring and Evaluation, and Providing Solutions and Recommendations. Overall, this assistance activity succeeded in improving the understanding, skills, and quality of packaging for the organic fertilizer product